Genetic Determinants of Musculoskeletal Adaptations To Unloading and Reloading - Özçivici, Engin; Özçivici, Engin; Judex, Stefan (Institute of Electrical and Electronics Engineers Inc., 2019)
Lack of weight bearing is one of the most critical limitations for long term health of bone tissue in space missions. In this study, we performed a series of Quantitative Trait Locus (QTL) analysis of musculoskeletal traits to define genomic modulators adaptations to mechanical unloading and subsequent reloading using a genetically heterogeneous (F2 BALBxC3H) female mouse population. The identified regions on genome contain genes that regulate musculoskeletal adaptations to weightlessness and further studies may help to categorize individuals that are at risk for greater tissue loss during weightlessness and/or low tissue recovery during reambulation.
9th International Conference on Recent Advances in Space Technologies (RAST) -- JUN 11-14, 2019 -- Istanbul, TURKEY
Keywords: Mechanical loading; QTL; Bone; Muscle; Stress